(untitled) (Journal of Parents and Teachers, 2015)
Through an educational trip, students in second year of Primary Education, had the opportunity to know first-hand the operation mode of schools in the rural area of northern Madrid. In these, various innovative methodologies were applied such as the dialogic learning and Montessori method. Different manifestations of the teachers and pupil´s behavior observed in them, could affirm the value and the importance of these new methodologies in the learning process.